Industrial biotechnology: from knowledge to products - Ibrahim Che Omar (Penerbit Universiti Malaysia Kelantan, 2019)
Industrial Botechnology is not a new area and has shown success for more than a few decades in developed countries. However, Malaysia remains to be the end user of the technologies developed by the scientists from those countries. Nevertheless, Industrial Biotechnology has always been one of the important reserach areas in Malaysia, although the real success is yet to be seen. This is based on the low number of biotechnological based industries in the country. However off late, the industries which are related to the use of enzymes and fermentation processes have increased significantly. The book provides an overview of the life time research contribution and achivements encompassing the enzyme production, applications and the enzyme technologies with special focus on the lipokytic and the lignocellulolytic enzymes from microbial sources.